PATENT PROTECTION FOR ARTIFICIAL INTELLIGENCE: A COMPARATIVE STUDY OF INDONESIA AND THE UNITED STATES - Rahmatillah, Raihan; Sanusi, Sanusi (Student Journal of International Law, 2024)
This study examines the patent protection of artificial intelligence (AI) under the laws of Indonesia and the United States, with a particular focus on the legal ambiguities surrounding the patentability of computer programs. The Indonesian Patent Act excludes mere computer programs from patent eligibility, but its explanatory notes suggest exceptions that create legal uncertainty. Similarly, the US Patent Act lacks explicit provisions addressing computer programs, leading to uncertainty regarding AI patent protection. Employing a normative legal research methodology and a comparative approach, this study assesses the adequacy of patent laws in both countries. Data is gathered through library research, official sources, and limited interviews. The findings indicate that while AI inventions receive some level of partial protection in both jurisdictions, the US system benefits from more established precedents and clearer standards. The study concludes with recommendations for Indonesia to enhance its patent framework by drawing lessons from the US approach. It emphasizes the need for clear, adaptable, and uniform patent regulations to promote AI innovation. Proposed reforms should include explicit provisions for recognizing computer programs and AI algorithms as patentable inventions, thereby ensuring legal certainty and fostering educational initiatives on AI patent protection.